Self-regulated learning among teacher education students: Motivational beliefs influence on the use of metacognition. Issue 6 (11th December 2017) - Muwonge, Charles Magoba; Schiefele, Ulrich; Ssenyonga, Joseph; Kibedi, Henry
Abstract : In the present study, we examined the relationships between motivational beliefs (self-efficacy, task value, and control of learning beliefs) and use of metacognitive learning strategies among teacher education students in Uganda. The sample comprised of 649 students selected from seven universities. Data were collected using several scales from the modified Motivated Strategies for Learning Questionnaire, and analysed using Structural Equation Modelling. Task value and self-efficacy independently and significantly predicted students' reported use of metacognition. Students' self-reported self-efficacy and task value explained 38% of the variance in their use of metacognition. The evidence suggests interventions aimed at improving teacher education students' metacognitive skills to focus on enhancing their efficacy and value beliefs.